Circulating microRNA profiles based on direct S‐Poly(T)Plus assay for detection of coronary heart disease - Su, Mingyang (J Cell Mol Med, 2020)
Coronary heart disease (CHD) is one of the leading causes of heart‐associated deaths worldwide. Conventional diagnostic techniques are ineffective and insufficient to diagnose CHD with higher accuracy. To use the circulating microRNAs (miRNAs) as non‐invasive, specific and sensitive biomarkers for diagnosing of CHD, 203 patients with CHD and 144 age‐matched controls (126 high‐risk controls and 18 healthy volunteers) were enrolled in this study. The direct S‐Poly(T)Plus method was used to identify novel miRNAs expression profile of CHD patients and to evaluate their clinical diagnostic value. This method is an RNA extraction‐free and robust quantification method, which simplifies procedures, reduces variations, in particular increases the accuracy. Twelve differentially expressed miRNAs between CHD patients and high‐risk controls were selected, and their performances were evaluated in validation set‐1 with 96 plasma samples. Finally, six (miR‐15b‐5p, miR‐29c‐3p, miR‐199a‐3p, miR‐320e, miR‐361‐5p and miR‐378b) of these 12 miRNAs were verified in validation set‐2 with a sensitivity of 92.8% and a specificity of 89.5%, and the AUC was 0.971 (95% confidence interval, 0.948‐0.993, P < .001) in a large cohort for CHD patients diagnosis. Plasma fractionation indicated that only a small amount of miRNAs were assembled into EVs. Direct S‐Poly(T)Plus method could be used for disease diagnosis and 12 unique miRNAs could be used for diagnosis of CHD.